Role of Geography Education in Raising Environmental Awareness: A Literature Review - Rakuasa, Heinrich; Latue, Philia Christi (PT. Riset Press International, 2024)
This research is a literature review that aims to explore the significant role of Geography Education in increasing environmental awareness. This research uses a descriptive Qualitative Method by conducting a literature study related to this research. The results of the literature analysis show that geography education provides an important foundation for students to understand the complex relationship between humans and the natural environment, as well as its impact on the sustainability of the Earth. In addition, it helps students identify global and local environmental problems, provides insight into workable solutions, and encourages an environmentally responsible attitude. This study confirms that geography education has great potential in shaping a generation that is environmentally conscious, ready to participate in nature conservation efforts, and address the increasingly pressing environmental challenges of the future.